PENGARUH UKURAN PERUSAHAAN, INTENSITAS PERSEDIAAN, FINANCIAL LEVERAGE, RASIO LANCAR, DAN STRUKTUR KEPEMILIKAN TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia 2014-2016) - Bambang Tugiyono, 13.05.52.0187; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2017)
The research aims to analyze the selection that influence a company's decision to use the methods of inventory valuation in its financial statements. The research examines five independent variables were it testedfirm size, the intensity of the inventory, financial leverage, current ratio, and the structure of ownership. While the dependent variable, namely the FIFO method of inventory valuation and average. The sampling method in this research using purposive sampling the study period of 2014 to 2016. The relationship and or influence between independent variables and the dependent variable is explained by using logistic regression analysis. The results of the study are as follows: the size of the company, ownership structure significantly influence the selection method of inventory accounting, whereas the intensity of the inventory, financial leverage, current ratio does not significantly influence the selection method of inventory accounting.Keywords: Company Size, Intensity Inventory, Financial Leverage, Current Ratio, Ownership Structure, Selection Inventory Accounting Method